“Dúthaigh Na Súpanna”: An Insight Into “Souper Territory” from the Folkloric Repertoire of Seán Mac Criomhthain - Mac An tSionnaigh, Seaghan (Studia Celtica Posnaniensia, 2019)
West Kerry storyteller Seán Mac Criomhthain (1873-1955) was born almost a quarter-century after the Great Irish Famine. Nevertheless, his upbringing occurred in a context which included both overt and covert references to the kinds of sectarian divisions which initially had contributed to the famine, and which later were entrenched by it. Sectarian division in the Irish context expressed itself primarily via denominational attachment, and to a lesser extent, along linguistic lines. Such divisions were explored across the country through traditional lore and through song; and in the specific repertoire of Seán Mac Criomhthain, through the medium of a mellifluous ‘brand’ of Munster Irish for which the Corca Dhuibhne peninsula has since become renowned. This article attempts to describe attitudes to sectarian division in the evidence of Mac Criomhthain’s repertoire. With extensive reference to a composition translated for the first time to English, it will be argued that concerns of immediate social pragmatism are afforded much greater importance than those of denominational or linguistic attachments.